Slovak Republic : Development Policy Review, Volume 1. Summary Report - World Bank (Washington, DC, 2013)
Although the unsustainably high external current account, and fiscal deficits may be financed with the country's capital account surplus (twenty percent of GDP), such situation is not likely to last. The country's policy impact on the real exchange rate, undermines the employability of large segments of the population, which will ultimately hamper growth. The study proposes an agenda on key issues, such as curtailing enterprise subsidies, and other guarantee payments, redirecting, rather than expanding, existing expenditure programs to meet the eligibility criteria for structural funds financing. In addition, further increasing the retirement age, would put public pensions on a sustainable footing, and avoid the massive fiscal deficits the demographic transition is bringing, and, postponing the revenue reduction (from 38 percent of GDP in 2000 to a projected 35 percent in 2002, to a target of 33 percent of GDP in 2004) until such time as the expected cutback in expenditure has actually materialized, should be part of the development agenda. The tax burden should be balanced away from payroll taxes, e.g., streamlining Value Added Tax (VAT) refunds, or trimming tax incentives for investment to European Union-compatible levels. Moreover, the planned increases in electricity, and natural gas tariffs should be brought forward, and, the internal trade border within the Czech-Slovak customs union should be brought down ahead of EU accession. Longer term reform efforts should focus on social protection, health care, and education, based on a governance approach built on transforming budget frameworks, consolidating decentralization efforts, and launching a major judicial reform.